Nutritional status of herbage and goats under different grazing management practices on semi-arid rangeland vegetation - Mahanta, S K; Pailan, G H; Verma, N C (The Indian Journal of Animal Sciences, 2012)
A grazing trial of 120 days duration was conducted in goats on rangeland vegetation to record herbage mass and its quality, and nutritional status of animals. Yearling female Barbari goats divided into groups G1, G2 and G3 of 9 animals each, were allowed to graze on 3 ha of vegetation (@ 9 animals/ha) during winter for 6.5 to 8 h daily following 3 different grazing management practices viz. continuous, rotational and deferred rotational, respectively. They were also supplemented with barley grain (@ 1.0% of body weight) as energy source. Availability of herbage mass (kg DM/ha) of grass dominated vegetation was comparatively higher (2910) under deferred rotational than rotational (2677) and continuous (2365) system of grazing management However, quality of herbage mass in terms of CP (4.57 to 4.70%), NDF (77.8 to 79.7%) and ADF (46.6 to 50.3%) was comparable among the different grazing management practices. Similarly average CP of mouth grab forage samples was comparable amongst the treatment groups and ranged from 10.7 to 11.9%. Daily feed (DM) intake was 506, 512 and 546 g in goats under G1, G2 and G3 groups, respectively, and the differences were nonsignificant among the groups. The digestibility of nutrients was statistically similar among the groups. Goats were also on similar plane of nutrition consuming comparable quantities of CP and TDN. Concentration of glucose, plasma protein and urea-nitrogen was similar in G1, G2 and G3 groups. It was concluded that at similar stocking rates, grazing management practices did not have any influence on herbage mass and its quality as well as nutrient utilization and blood metabolites in goats allowed to graze on rangeland vegetation of Bundelkhand with supplementation of barley.